Larval growth rate is not a major determinant of adult wing shape and eyespot size in the seasonally polyphenic butterfly Melanitis leda - Freerk Molleman; M. Elizabeth Moore; Sridhar Halali; Ullasa Kodandaramaiah; Dheeraj Halali; Erik van Bergen; Paul M. Brakefield; Vicencio Oostra (PeerJ, 2024)
Background Insects often show adaptive phenotypic plasticity where environmental cues during early stages are used to produce a phenotype that matches the environment experienced by adults. Many tropical satyrine butterflies (Nymphalidae: Satyrinae) are seasonally polyphenic and produce distinct wet- and dry-season form adults, providing tight environment-phenotype matching in seasonal environments. In studied Mycalesina butterflies, dry-season forms can be induced in the laboratory by growing larvae at low temperatures or on poor food quality. Since both these factors also tend to reduce larval growth rate, larval growth rate may be an internal cue that translates the environmental cues into the expression of phenotypes. If this is the case, we predict that slower-growing larvae would be more likely to develop a dry-season phenotype. Methods We performed the first experimental study on seasonal polyphenism of a butterfly in the tribe Melanitini. We measured both larval growth rate and adult phenotype (eyespot size and wing shape) of common evening brown butterflies (Melanitis leda), reared at various temperatures and on various host-plant species. We constructed provisional reaction norms, and tested the hypothesis that growth rate mediates between external cues and adult phenotype. Results Reaction norms were similar to those found in Mycalesina butterflies. We found that both among and within treatments, larvae with lower growth rates (low temperature, particular host plants) were more likely to develop dry-season phenotypes (small eyespots, falcate wing tips). However, among temperature treatments, similar growth rates could lead to very different wing phenotypes, and within treatments the relationships were weak. Moreover, males and females responded differently, and eyespot size and wing shape were not strongly correlated with each other. Overall, larval growth rate seems to be weakly related to eyespot size and wing shape, indicating that seasonal plasticity in M. leda is primarily mediated by other mechanisms.